2012
DOI: 10.1007/s10334-012-0309-8
|View full text |Cite
|
Sign up to set email alerts
|

Arterial spin labeling: its time is now

Abstract: It has been more than two decades since arterial spin labeling (ASL) perfusion MRI was introduced [1,2], yet its impact on research and clinical studies is just starting to be broadly appreciated. ASL has gone from an infancy where it was practiced in small animals by just a few experts, to a childhood of initial experience in humans and in more laboratories, and finally through an awkward adolescence where emerging capabilities were masked by imperfect coordination of methods, analysis, and distribution. As e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Ten averages were acquired, resulting in scan duration of 1.5 min. The PC slice was placed 2mm distal to the left carotid artery bifurcation and oriented perpendicular to the internal carotid and vertebral arteries, allowing simultaneous assessment of the four feeding vessels [36]. The slice was positioned based on a time-of-flight MRA sequence (TR/TE: 17 msec/4.12 msec, FA: 18°, voxel size: 1 × 1 × 2.5 mm 3 , 40 slices, one saturation band placed above the imaging slab, acquisition time: 2.9 min).…”
Section: Methodsmentioning
confidence: 99%
“…Ten averages were acquired, resulting in scan duration of 1.5 min. The PC slice was placed 2mm distal to the left carotid artery bifurcation and oriented perpendicular to the internal carotid and vertebral arteries, allowing simultaneous assessment of the four feeding vessels [36]. The slice was positioned based on a time-of-flight MRA sequence (TR/TE: 17 msec/4.12 msec, FA: 18°, voxel size: 1 × 1 × 2.5 mm 3 , 40 slices, one saturation band placed above the imaging slab, acquisition time: 2.9 min).…”
Section: Methodsmentioning
confidence: 99%
“…To minimize these static tissue signals, background suppression techniques were developed (95, 96). Since background suppression does reduce ASL signals, there is still debate as to whether or how much background suppression to use (97). Furthermore, the labeling pulse can cause substantial magnetization transfer (MT) effects in the static tissue of the image slices, particularly with CASL, due to the long labeling.…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of studies have suggested that ASL CBF may be sensitive to neurometabolic alterations among persons with risk factors for AD including individuals with mild cognitive impairment (MCI;Johnson et al 2005;Xu et al 2007;Chao et al 2009;Dai et al 2009;Bangen et al 2012) and cognitively normal adults who have a FH of AD and/or carry the APOE4 allele (Fleisher et al 2009;Filippini et al 2011); with the latter set of studies yielding inconsistent findings. However, only recently has the ASL methodolgy become more fully developed and readily available across major scanner vendors (Alsop 2012), suggesting the need for a renewed evaluation of the utility of ASL CBF within the context of AD, from its preclinical stages to frank dementia. Therefore, in this cross-sectional study, we used a whole-brain CBF sequence with established fidelity (Gevers et al 2011) to evaluate resting CBF in a large sample (n = 327) of wellcharacterized adults spanning the AD spectrum from at-risk cognitively healthy middle-aged individuals to patients with probable AD.…”
Section: Introductionmentioning
confidence: 99%